SEMANTIC RELATIONS: GRADUONYMY - Matkarimova Shokhista; Qurbanbayeva Mohinur (Journals Park Publishing, 2024)
It is well known that all languages have words that consist of semantic relations which are help to construct sentences in plethora type of ways. For instance, they give a chance to introduce deeper descriptions of sentences. Also, they discussed by literally, figuratively and meaning of context or semantics can utilize in philosophical issues. This article illustrates one of the semantic relation that phenomenon of graduonymy, their use and similarities and differences from other semantics.
Keywords: linguistic, graduonymy, grading, lexema, lexical semantic, graduonymic row, communication verbs, activity verbs, mental verbs, causative verbs, synonyms.